2011
DOI: 10.3341/jkos.2011.52.10.1135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Dry Eye Syndrome in the Incheon Area

Abstract: Purpose: To investigate the prevalence, clinical manifestations, and risk factors of dry eye syndrome (DES) among people over 50 years old in the Incheon area. Methods: A cross-sectional prevalence study was performed on 462 people over 50 years old in Dong-gu, Incheon. DES was defined as the constant or frequent presence of symptoms of both dryness and irritation. Symptoms and past medical history were assessed by a survey. Eye examination included slit lamp examination, Schirmer test, and tear break-up time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
2
1
1
Order By: Relevance
“…Although some previous studies found no association between aging and the prevalence of dry eye disease [5,9,15,16], other studies showed that the prevalence of dry eye disease increases with age [6,17]. However, our study showed that the prevalence and OR of dry eye symptoms tended to decrease with age.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Although some previous studies found no association between aging and the prevalence of dry eye disease [5,9,15,16], other studies showed that the prevalence of dry eye disease increases with age [6,17]. However, our study showed that the prevalence and OR of dry eye symptoms tended to decrease with age.…”
Section: Discussioncontrasting
confidence: 94%
“…A study of people aged ≥65 years in the Yongin area using a six-item questionnaire to assess dry eye symptoms found a crude prevalence of 30.3% [7]. Another community-dwelling populationbased study of people aged ≥50 years in the Incheon area found the prevalence of dry eye symptoms to be 26.2% [9]. That study used a selfadministered six-item questionnaire similar to the one used in the Yongin study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…안구건조증 설문 안구건조증은 안구표면질환지수(ocular surface disease index, OSDI)를 사용하여 새건물에서 근무하게 된 이후에 느끼게 된 자각증상을 조사한 후 점수로 환산하였다. [9][10][11] OSDI는 12개의 문항과 각 문항당 4점 척도로 구성되어 [20] 특히, 사무실 근 로자의 업무실적을 저하시키는 내부적인 환경요소로 작용 할 수 있을 것이다. [19] 최근의 연구에서 안구건조증은 작업 실적과 일상활동에 유의한 영향을 미친다고 보고되었다.…”
unclassified